Effect of time, temperature and pH on crude oil biodegradation by bacterial isolates from Al- Dora refinery- Baghdad - Melad K.Mohammed; Saad H. Khudaier; Ithar kamil Al-Mayaly; Shihab A. Salman (Al-Qadisiyah Journal of Pure Science, 2018)
Bacterial isolates Pseudomonas aeruginosa , Bacillus cereus and Bacillus subtilis were isolated from wastewater treatment plant of Al- Dora refinery and used to study the optimal conditions ( time , temperature and pH ) for biodegradation of crude oil . Liquid BH medium with 1% crude oil was used in these experiments , 25 ml Erlenmeyer flask with 1% crude oil at different pHs ( 4 - 10 ) were inoculated by the three bacterial isolates and incubated at different period ( 1 - 10 ) days and different temperature ( 25 - 45¢ªC ). Results shown that P. aeruginosa degraded a maximum of (72%) of crude oil when grown in the medium at initial pH of 8 and incubated at 30 ¢ªC for 6 days , while B. subtilis and B. cereus shown ( 65%) and (55%) of crude oil degradation respectively when grown in BH medium, pH 8 and incubated at 30 ¢ªC for 6 days . Results also indicated that the three isolates gave a significant reduction in surface tension of medium and the P. aeruginosa showed the high ability to decrease the surface tension from ( 73 - 24 mN/m) compared with other two isolates .